2017
DOI: 10.1088/1361-6641/aa8b2c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deposition temperature on the properties of SnS thin films grown over silicon substrate—comparative study of structural and optical properties with films grown on glass substrates

Abstract: Tin sulfide (SnS) thin films were chemically deposited over silicon substrate in a temperature range of 250 °C-400 °C. The effects of deposition temperature on the structural, morphological and optical properties of the films were evaluated. All films present an orthorhombic SnS structure with a preferred orientation along (040). High absorption coefficients (in the range of 10 5 cm −1 ) were found for all obtained films with an increase in α value when deposition temperature decreases. Furthermore, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In all the deposited layers, Raman mode appeared at 94 cm -1 had the highest intensity compared to other modes. A similar trend of Raman spectra with 94 cm -1 as an intense peak was observed by Sall et al [52] in SnS films prepared by chemical spray pyrolysis. Arulantham et al [63] also observed a strong Raman mode at 94 cm -1 in SnS thin films prepared by nebulizer spray pyrolysis technique.…”
Section: Raman Analysissupporting
confidence: 86%
See 3 more Smart Citations
“…In all the deposited layers, Raman mode appeared at 94 cm -1 had the highest intensity compared to other modes. A similar trend of Raman spectra with 94 cm -1 as an intense peak was observed by Sall et al [52] in SnS films prepared by chemical spray pyrolysis. Arulantham et al [63] also observed a strong Raman mode at 94 cm -1 in SnS thin films prepared by nebulizer spray pyrolysis technique.…”
Section: Raman Analysissupporting
confidence: 86%
“…Among these modes, 12 are Raman active (4A g , 2B g, 4B 2g and 2B 3g ), 7 are infrared active (3B 1u , 3B 3u and 1B 2u ), and 2 are inactive (2A u ) [60] . The observed Raman modes at 94, 219 and 225 cm -1 were assigned to A g [52] whereas the mode present at 166 cm -1 was assigned to B 3g [61] and the mode at 178 cm -1 was assigned to B 2g [52] . The observed Raman modes are in good agreement with the reported data on SnS layers [52,[60][61][62][63] .…”
Section: Raman Analysismentioning
confidence: 90%
See 2 more Smart Citations
“…As a matter of fact, the use of these compounds has posed new challenges for several research groups. Therefore, a variety of phosphorus compounds have been exploited to deposit binary semiconductor materials such as: dichalcogeno-imidodiphosphate molecules and its derivatives R 2 (E)PNHP(E)R 2 (E=O, S, Se, Te, R=alkyl, aryl, alkoxy) [3], cyclohexylphosphine compounds such as (C 6 H 11 )PH 2 ) [4] and triphenylphosphine chalcogenides such as Ph 3 PS [5] and Ph 3 PSe [6]. Others phosphorus complexes such as [Pb((S)PPh 2 ) 2 N) 2 ], [Pb((Se)PPh 2 ) 2 N) 2 ] [7] [Sb(S 2 P(OR) 2 )] 3 [8], [In(iPr 2 PSe 2 ) 3 ] and [Cu 4 (iPr 2 P 2 Se 2 ) 4 ] [9] have been also used as single-source precursors.…”
Section: Introductionmentioning
confidence: 99%